Response to increasing levels of NK in the production of onion (Allium cepa L.) var. “Roja Arequipeña” - Amaya, Julio (2013)
With the objective to determine the influence of increasing levels of nitrogen and potassium in the growth and yield of onion bulbs, an experiment was carried in the Experimental Institute for Agricultural Research and Technology located in Pampas de San Juan, Laredo, La Libertad (Peru). The experimental design was randomized complete block with 3x4 factorial arrangement with three replicates and twelve treatments resulting from combinations 60, 120, 180 and 240 kg N ha-1 , and 40, 80 and 160 kg K2O has -1 , using 80 kg as a single dose of P2O5.ha-1 . We used certified seed onion var. "Roja Arequipeña”. Linear responses were obtained for the weight of bulbs with yields of 1.010 and 1.006 g -1 average of 10 bulbs, with combinations of N120xK80 x K80 and N60, and quadratic response to N dose of 120 kg.ha-1 with which promoted the increased production of onion bulbs.